Imprisonment and women's health: concerns about gender sensitivity, human rights and public health - Brenda J van den Bergh; Alex Gatherer; Andrew Fraser; Lars Moller (The World Health Organization, 2011)
The health of prisoners is among the poorest of any population group and the apparent inequalities pose both a challenge and an opportunity for country health systems.The high rates of imprisonment in many countries, the resulting overcrowding, characteristics of prison populations and the disproportionate prevalence of health problems in prison should make prison health a matter of public health importance. Women prisoners constitute a minority within all prison systems and their special health needs are frequently neglected. The urgent need to review current services is clear from research, expert opinion and experience from countries worldwide. Current provision of health care to imprisoned women fails to meet their needs and is, in too many cases, far short of what is required by human rights and international recommendations. The evidence includes a lack of gender sensitivity in policies and practices in prisons, violations of women's human rights and failure to accept that imprisoned women have more and different health-care needs compared with male prisoners, often related to reproductive health issues, mental health problems, drug dependencies and histories of violence and abuse. Additional needs stem from their frequent status as a mother and usually the primary carer for her children. National governments, policy-makers and prison management need to address gender insensitivity and social injustice in prisons. There are immediate steps which could be taken to deal with public health neglect, abuses of human rights and failures in gender sensitivity.